Water- and Base-Extractable Organic Matter in Sediments From Lower Yangtze River–Estuary–East China Sea Continuum: Insight Into Accumulation of Organic Carbon in the River-Dominated Margin - Han, Lulu; Wang, Yinghui; Xu, Yunping; Wang, Yasong; Zheng, Yiling; Wu, Jianqiang (Frontiers in Marine Science, 2021)
The burial of organic carbon (OC) in the river dominated margin plays an important role in global carbon cycle, but its accumulation mechanism is not well understood. Here, we examined the concentration and distribution of water extractable organic matter (WEOM) and base extractable organic matter (BEOM) in surface sediments from the lower Yangtze River, estuary and East China Sea. The chemical characteristics of the WEOM and BEOM were described by multiple ultraviolet-visible and fluorescence spectral indicators. Concentrations of both WEOM and BEOM showed significant correlations with sediment grain size, suggesting that mineral surface area is a key factor for OC loadings on sediments. However, compositions of WEOM and BEOM were related to salinity and sediment grain size, respectively. Three components (C1, C2 and C3) extracted from fluorescence excitation emission matrices-parallel factor analysis were assigned as terrestrial humic-like substance, mixed terrestrial/aquatic humic-like substance, and microbial tryptophan-like substance, respectively. From the lower Yangtze River to East China Sea, the decrease of C1%, SUVA254 and HIX, and the increase of C3%, FI and BIX in WEOM suggested the loss of terrestrial OC and addition of microbial OC. While for BEOM, the overall increase of C1% and HIX as well as the decrease of C3% and FI suggested selective removal of fresh, algal OC and preferential preservation of terrestrial OC. Our study demonstrates complex behaviors of sediment organic matter during the land-to-sea transport that was largely controlled by the binding strength of organic matter-sediment association, and that the formation of BEOM is an important pathway for accumulation of terrestrial organic matter in the river dominated margin.